The Role of DNA‐Stained Currency in Gang Robberies within the United Kingdom1. Issue 1 (3rd October 2013) - Mead, Breanna K.; Hayward, James; Liang, Benjamin; Wan, MeiLin; Benson, Tony; Karp, Jennifer
Abstract Cash‐and‐valuables‐in‐transit (CViT) robberies have become a substantial problem—especially in the current global economy. Over £19.4 million were stolen in 2008 and £17.1 million in 2009 in the United Kingdom alone. The transportation of cash and valuable items between financial institutions has long been a target of robberies in the U.K. After a robbery has occurred, police collect evidence in the form of ink‐stained currency. These stained notes are submitted for analysis. Samples are subjected to polymerase chain reaction in order to amplify any possible botanically derived DNA markers present on the notes. After amplification, capillary electrophoresis allows for the deciphering of the "DNA profile." The DNA profile is then linked to a particular cash box, and this information is compared with records of whether or not that box had been stolen. The cases below are three such instances where botanically marked currency was used to help solve robberies.